Interpretasi Teori Dramatisme dalam Nilai-nilai Film How to Make Million Before Grandma Dies - nirwasita, Nadia rashifa; Saputra, Muhammad Aditya (Sadharananikarana: Jurnal Ilmiah Komunikasi Hindu, 2024)
Research on Dramatism Theory from Kenneth Burke in the film How to Make a Million Before Grandma Dies explains that it contains a package of interpretations of the reality of everyday life. The main discussion regarding this research shows the effects felt by the audience after the film has finished playing. By reflecting on this film, it can be concluded that people can use this film as a lesson in living their daily lives. By applying Dramatism Theory in the analysis of this film, it is hoped that people will be aware of what is contained in their own lives. The explanation and application of Dramatism Theory in everyday life is seen from how humans as the main actors can balance drama agreements and scenarios in their own lives.